Avaliação das respostas cardiovasculares à medida de pressão expiratória máxima estática e à manobra de Valsalva em homens saudáveis - Minatel, Vinicius (2013)
The assessment of respiratory muscles by the measure of maximal inspiratory (MIP) and expiratory (MEP) pressures, have been routinely applied in the physical therapy clinical practice. However, these measures, especially MEP, have been contraindicated in some situations because it is believed that the cardiovascular responses obtained in MEP are similar to found during Valsalva maneuver (VM). So, based in these similarities between the responses two studies were done. The first study had as principal purpose to evaluate the heart rate (HR) during MEP and VM in healthy young, at different postures, to identify whether and in which situation the MEP reproduces the responses obtained in VM and additionally, to estimate the workload (W) realized during the maneuver. Twelve healthy young men (25±2 years) participated in this study and were evaluated, instructed and familiarized with the maneuvers, which were performed at supine and sitting positions. The VM was characterized by an expiratory effort (40 mmHg) against a manometer for 15 s. The MEP measure has been performed according to the American Thoracic Society. The results obtained in this study show that heart rate variation (ΔHR) was not influenced by the position, and during VM, the ΔHR and the Valsalva index (VI) were higher than the ΔHR and MEP index (MEPI) values (p<0.001). Besides, the estimated workload of the maneuvers was statistically different (p<0.001) between the maneuvers, being that the Wtotal was higher in VM and the Wisotime and Wisotime/ΔFCisotime were higher in MEP. Based in these results it could be concluded that in the study conditions the MEP does not reproduces the HR response observed in the VM in healthy young men. However, the results obtained in the first study allowed comparing only the cardiac stress generated by the maneuvers in a specific age, doing that the blood pressure (BP), cardiac output (CO), stroke volume (SV) and peripheral vascular resistance (PVR) responses remain unknown. Furthermore, little is known about the cardiovascular response during MEP measure in others age and distinct clinical conditions, once that aging process promotes important structural and functional alterations in the respiratory, cardiovascular and autonomic systems. Therefore, the second study had as main purpose to compare the cardiovascular response by the analysis of mean arterial pressure (PAM), CO, SV, HR and PVR, during VM and MEP. In addition to evaluate the effect of aging process over the cardiovascular responses obtained during the different maneuvers by the young (YG) and middle-age group (MAG). Twenty-eight healthy volunteers of male gender participated in this study and were divided in two groups: YG (n=15) and MAG (n=13) with mean age of 25±5 years and 50±5 years, respectively. All volunteers were evaluated, instructed and familiarized with the maneuvers (VM and MEP), which were performed at sitting position following the same procedure used in the first study. The main results of this study show that: there isn t difference between CO responses during the maneuvers (p>0.05); the PAM responses (PAMpeak, PAMisotime, ΔPAM and ΔPAMisotime) and PVR (PVRisotime e ΔPVRisotime) were higher during MEP measure, differently of SV (SVpeak, SVnadir, ΔSV) and HR (HRpeak, HRnadir, HRisotime, ΔHR, ΔHRisotime and VI) which were higher during VM. Furthermore, it was observed that the MEP and PAM values were not influenced by the group (p>0.05), and the MAG have lower values than the YG to CO, HR, SV except to PVR. So, based in these results it could be concluded that the MEP measure generates cardiovascular responses similar to that observed during VM, relative to the CO, and higher values of PAM than that observed in VM. Besides, the maneuver execution time seems to be the great responsible for the activation of different physiological mechanisms involved on the control of these responses. Furthermore, it seems like the aging influences the HR and PVR responses during MV and MEP.